The Influence of Social Media on Career Choices in High School - Prameswari, Revita Ayodya; Yuliejantiningsih, Yovitha; Setyoningsih, Yunitha Dwi (International Journal of Applied Guidance and Counseling, 2026)
Social media has become one of the main sources of information for students in learning about education and careers. This study aims to determine the effect of social media use on the career choices of 11th grade students at Sultan Agung 01 Islamic High School in Semarang. This study uses a quantitative approach with a correlational design. The sample consisted of 152 students selected through simple random sampling. The instruments used were a social media usage scale and a career choice scale. Data analysis used a simple linear regression test with the help of SPSS version 22. The results showed a significant negative influence between social media usage and students' career choices, with a correlation coefficient of -0.465 and a significance of 0.000. The regression equation obtained, Y = 175.743 – 1.016X, shows that an increase in social media use is associated with a decrease in the accuracy of career choice, which is likely influenced by the dominance of non-educational content. These findings indicate that the higher the use of social media, the lower the accuracy of students' career choices. Therefore, it is necessary to strengthen digital literacy and the role of guidance and counseling services by integrating social media as a means of targeted and educational career guidance, rather than limiting its use.